ANALISIS PENGGUNAAN LAHAN PERTANIAN DI KAWASAN LINDUNG DAS SAMIN UNTUK MITIGASI BENCANA LONGSOR DAN BANJIR - Robertus Sudaryanto (Faculty of Agriculture, Universitas Sebelas Maret, 2010)
Title : The Analysis of Agricultural Land Use in Protected Areas Watershed Samin for Landslide and Flood Disaster Mitigation. This study aims to analyze the protected areas Samin watershed which use for agriculture. Research done by interpretation of the Rupa Bumi Indonesian Map, Aerial Photos and Google Earth, continued by the field observation. From this study were concluded that the protected area with slope > 45% majority have used by agriculture, while the soil is dominated by Alfisol and Andisol,which have easily eroded and prone to landslides. Most of local protected areas (rivers basin) had disfunction and it is dominated by Entisol.The mentioned cause Samin watershed gristle of floods, dryness dan landslide disaster. Suggested to the local government to consider the revitalization of the protected areas Samin watershed. Keywords: agriculture, disaster mitigation, flood, landslide, Samin Watershed